The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/ac200693h
|View full text |Cite
|
Sign up to set email alerts
|

Brominated Tyrosine and Polyelectrolyte Multilayer Analysis by Laser Desorption Vacuum Ultraviolet Postionization and Secondary Ion Mass Spectrometry

Abstract: The small molecular analyte 3,5-dibromotyrosine (Br2Y) and chitosan-alginate polyelectrolyte multilayers (PEM) with and without adsorbed Br2Y were analyzed by laser desorption postionization mass spectrometry (LDPI-MS). LDPI-MS using 7.87 eV laser and tunable 8 – 12.5 eV synchrotron vacuum ultraviolet (VUV) radiation found that desorption of clusters from Br2Y films allowed detection by ≤8 eV single photon ionization. Thermal desorption and electronic structure calculations determined the ionization energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Overall, 10.5 eV photon energy displayed an optimal balance between sensitivity and fragmentation, in agreement with prior experiments. 26, 27, 35 Similar conclusions were reached from 7.87 – 10.5 eV synchrotron LDPI-MS of E. coli (tomato strain) monoculture blots (full mass spectra shown in Supplementary Information). The mass spectral peaks observed for E. coli and yeast monocultures were tabulated with the VUV photon energies at which they were first observed by synchrotron LDPI-MS (see Supplementary Information).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Overall, 10.5 eV photon energy displayed an optimal balance between sensitivity and fragmentation, in agreement with prior experiments. 26, 27, 35 Similar conclusions were reached from 7.87 – 10.5 eV synchrotron LDPI-MS of E. coli (tomato strain) monoculture blots (full mass spectra shown in Supplementary Information). The mass spectral peaks observed for E. coli and yeast monocultures were tabulated with the VUV photon energies at which they were first observed by synchrotron LDPI-MS (see Supplementary Information).…”
Section: Resultssupporting
confidence: 73%
“…Prior control experiments with the 10.5 eV laser LDPI-MS established the presence of single photon ionization and ruled out both direct ions from laser desorption and photoelectron ionization effects due to the residual 355 nm beam used to generate VUV radiation. 25 Photoelectron ionization was previously ruled out in the synchrotron LDPI-MS. 27 The similarity of the spectra of 7.87 eV synchrotron and laser LDPI-MS ruled out photoelectron ionization in the latter case.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Several peaks at m/z 270.1 and below m/z 150 appeared from desorption laser-induced pyrolysis of the multilayer. 9 The bottom and top traces show mass spectra before and after UV sterilization, respectively, again indicating no significant differences in the fragmentation pattern of MPA-ampicillin. It is concluded that photolysis or other modification of the antibiotic or multilayer did not result from UV sterilization.…”
Section: Resultsmentioning
confidence: 94%